Edukasi Penyakit Menular serta Pencegahan TBC melalui Tes Cepat Molekuler (TCM) - Pipin Sumantrie; Martalina Limbong; Julianto Julianto (Universitas Muhammadiyah Semarang, 2023)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, this disease is common in developing countries with tropical climates. This disease is widely suffered by various groups of people, both the lower class, middle class, upper class society, and even the elite who are infected with this disease. This is a serious concern of the government, through the Ministry of Health of the Republic of Indonesia, in order to prevent it. The method used in community service activities is to provide assistance to the community, as well as infection prevention training through Rapid Molecular Test (TMC) examinations, for participants, consisting of 92 nursing students. The conclusions drawn from this activity were as follows, as a whole (100%) participants understood about healthy living behaviors, and prevention of TB infectious disease, and the results of TB examinations found no one infected with the Mycobakterium Tuberculosis virus.